Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3917/edd.271.0127
|View full text |Cite
|
Sign up to set email alerts
|

Les déterminants du rendement scolaire en mathématiques chez les élèves de l'enseignement secondaire collégial au Maroc : une analyse multiniveaux

Abstract: L’objectif de cet article est d’identifier les facteurs qui expliquent la performance en mathématiques des élèves de niveau secondaire collégial marocain. Il s’appuie sur les résultats du programme TIMSS 2003 d’évaluation du niveau en mathématiques des élèves dans plusieurs pays. Les données utilisées portent sur un échantillon de 1 140 élèves relevant de 68 établissements scolaires répartis sur le territoire marocain. Nos résultats montrent que les performances sont expliquées essentiellement par le genre de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several studies have shown the important role of the learner in the process of competencies acquisition [16]- [18].…”
Section: Impact Of the Input Competence Factor: Results And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the important role of the learner in the process of competencies acquisition [16]- [18].…”
Section: Impact Of the Input Competence Factor: Results And Discussionmentioning
confidence: 99%
“…In a study using a multilevel model to identify the most important variables affecting students' performance [16], the authors have found evidence that both the students' and their families' characteristics play a role in the former's performance.…”
Section: Impact Of the Input Competence Factor: Results And Discussionmentioning
confidence: 99%
“…According to them, the mother's education does not have explanatory power on the children's school performance. This result is explained by the fact that in the sample studied (in a large city, Rabat in 1993), women with a high level of education were more engaged in professional life and entrusted the monitoring and support of their children to household helpers, often illiterate (Mourji and Abbaia, 2013). Hungi and al (2017) show that the level of education of the mother influences the performance of students in mathematics, but not in English in Uganda.…”
Section: ) Review Of the Literaturementioning
confidence: 95%